Supercritical Water Gasification of glycerol: Continuous reactor kinetics and transport phenomena modeling. (February 2022) - Salierno, Gabriel; Marinelli, Fabrizio; Likozar, Blaž; Ghavami, Niloufar; De Blasio, Cataldo
Highlights: Glycerol Supercritical Water Gasification of is done at 25 MPa and 610 °C in continuous operation. A non-isothermal compartment model is applied to explain gas productivity at low residence time. The influence of Stainless Steel 316 and Inconel-625 as reactor wall materials is compared. Catalytic effect of Inconel-625 explains the difference between both reactor materials. Inconel-625 produces 50% more C2 hydrocarbons and 40% more CH4, reducing a 50% the H2 yield. Abstract: Supercritical Water Gasification of glycerol is carried out on a continuous tubular reactor at 25 MPa and 610 °C. A design of experiments is performed at three levels of glycerol concentration (2.5; 5; and 10%) and three levels of inflow rate (125; 250; and 375 mL/min). The process outputs are the molar production of H2 ; CH4 ; CO2 ; CO; and C2 H6 . The influence of Stainless Steel 316 and Inconel-625 as reactor materials is compared. A compartment model is implemented considering the system as a heat exchanger in series with a wall reactor. Heat transfer influence on reactivity is successfully captured. The results are useful and accurate in describing global stoichiometry. H2, CH4, and CO2 productivity are fairly predicted. The catalytic effect of Inconel-625 manifests from the CO2 to CO ratio when compared with Stainless Steel 316. Inconel-625 is 50% more productive in terms of C2 hydrocarbons and 40% more active towards CH4 production, which is detrimental in 50% of the H2 yield. Graphical abstract: Image, graphical abstract